Polyvinylidene fluoride (PVDF) membrane for oil rejection from oily wastewater: A performance review. (December 2016) - Otitoju, T.A.; Ahmad, A.L.; Ooi, B.S.
Highlights: PVDF membranes for oil removal from wastewater. Advances in the performance of PVDF membranes for oil removal from wastewater. Low oil adhesive PVDF membrane fabrication remains a challenge and a prospect for future research. Novel non-solvent induced phase separation needs to be assessed. Abstract: The rapid rise in environmental awareness, tighter regulation, novel strategies to separate oils from industrial wastewater, polluted oceanic waters, and oil-spill mixtures, especially in the presence of surfactants have prompted the developments of novel membranes that are capable of separating oil from oily wastewater. Among numerous polymeric membranes, polyvinylidene fluoride (PVDF) membrane has been widely employed due to its outstanding properties. This review maps out the current trends and development as well as provides a perspective on potential outlook for advances in novel PVDF membrane for oil separation from oily wastewater. Despite the existing trends, there is still a challenge to produce membranes with low oil adhesive and anti-fouling properties, chemical resistance, high mechanical strength, high flux, high oil separation efficiency and long term stability during oily wastewater treatment. Fouling still remains a major dilemma restricting PVDF membranes towards their transition from laboratory to industrial scale application. To properly address this threat, there is need for researches into effective materials that can mitigate fouling phenomenon efficiently. In addition, a much stronger understanding of the basic properties of such materials will be required in order to find the relationship among the material properties, membrane morphology and the transport phenomena in the PVDF membrane. At the same time, the potential of novel non-solvent induced phase separation needs to be assessed as a comprehensive understanding between structure-surface properties and their performance for oily wastewater separation should be the backbone for future development and progress in PVDF membrane fabrication for oily wastewater treatment.